Implementasi Metode Waterfall dalam Sistem Informasi Knowledge Management untuk Digital Marketing - Chasanah, Nur; Diantono Abda’u, Prih; Nur Faiz, Muhammad (Infotekmesin, 2021)
The development of digital technology directs organizations to be able to cultivate knowledge as an asset that can help its business activities. Knowledge management is considered necessary to be implemented in organizations involving many stakeholders. The implementation of annual management needs to be implemented by involving the utilization. This research was conducted to implement knowledge management in organizations that involve many knowledge assets in the business process, especially related to digital marketing activities. The purpose of this research is to identify organizational knowledge and produce knowledge sharing media systems. This research uses waterfall method in the development of its system so that the result of this research is a knowledge management information system that facilitates knowledge sharing activities that have been identified and can facilitate users in finding data, information and knowledge that is useful in fostering innovations related to digital marketing in the organization.